ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PENGGUNA FINTECH DI KOTA BATAM - Nataliya, Veronica; Ompusunggu, Hermaya (LPPM Universitas Putera Batam, 2025)
This study examines the factors influencing MSMEs' interest in adopting fintech services in Batam City. Data was collected through online questionnaires and direct interactions, targeting 81,486 MSMEs registered with the Batam Cooperative Office. From this population, 100 respondents were selected using Slovin's formula to ensure representativeness. Statistical methods such as multiple linear regression and hypothesis testing were used, with SPSS version 29 ensuring accurate results. The findings show that the ease of using fintech significantly influences MSMEs' interest, as these services simplify financial management in a practical and efficient way. However, risks such as potential losses from system errors, hacking, or fraud remain major concerns that hinder adoption. Trust also plays a critical role, encompassing aspects like security, the provider's reputation, user experiences, and caution regarding financial risks. Building trust through transparency, user education, and quality customer service can encourage more MSMEs in Batam to embrace fintech services